KEADAAN FAKTOR PRODUKSI PADA USAHA GALANGAN KAPAL KAYU - Jasmoro, Jasmoro; Ahmad, Muchtar (Jurnal Perikanan dan Kelautan, 2009)
Understanding of industrial situation in an area, is essential to develop theindustry further, and production factors situation can be represent it. Usingendogenous perceptional method, the production factors of wooden made boat ofshipyard surveyed. The location, worker, capital, and entrepreneurship situation andcondition observed, were tend to be bad, due to the technical and managerialproblems. Especially concerning with entrepreneurship, high price and difficult to getproper wood materials, no well trained technician in ship design, in machineryrecruitment, and lack of training program to improve the situation or to solve theproblems. As consequence some of the shipyard enterprise either close, stop toproduce ship, or moving to other location. A deindustria-lization trend emerged asmany workers unemployed and the area become depressed.